2004
DOI: 10.1111/j.1440-1746.2004.03410.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver iron deposits in hepatitis B patients: Association with severity of liver disease but not with hemochromatosis gene mutations

Abstract: Elevated TS and liver iron deposits were frequent in non-cirrhotic HBV patients. Iron deposits were mainly mild and associated with higher activity and severity of liver disease, but not with HFE mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 37 publications
(109 reference statements)
7
51
0
1
Order By: Relevance
“…In contrast to C282Y mutation, H63D was more common in most of studies from India [5,8,18,19]. The overall allele frequency of H63D mutation was 5.26 (4.58 in controls and 5.95 in patients) which is quite similar to the previously reported studies by Panigrahi et al and Milman et al [17,20] but lesser than the others [8,13,25].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to C282Y mutation, H63D was more common in most of studies from India [5,8,18,19]. The overall allele frequency of H63D mutation was 5.26 (4.58 in controls and 5.95 in patients) which is quite similar to the previously reported studies by Panigrahi et al and Milman et al [17,20] but lesser than the others [8,13,25].…”
Section: Discussionsupporting
confidence: 82%
“…For example, high levels of serum ferritin and transferrin have been reported in these patients (13,33), although the causes of the increased serum ferritin and transferrin saturation remain unclear. Our observation that LHBsAg inhibited transferrin uptake by human hepatocytes provides a clue to the cause of the disordered metabolism of iron ions.…”
Section: Discussionmentioning
confidence: 99%
“…Yonal et al reported elevated serum transferrin saturation and ferritin concentration in patients with hepatitis B virus (HBV)-related liver disease [17]. Matinelli et al found elevated transferrin saturation in 27.1% of investigated HBV patients and increased liver iron deposition in 48.7% of the same cohort [18]. Hepcidin, a liver-produced peptide, is considered as the major control of body iron status.…”
Section: Introductionmentioning
confidence: 99%